The Dynamics of US Arms Sales to Taiwan: From the F-16 C/D Fighter Jets Rejection to F-16 Viper Fighter Jets Sales - Alkatiry, Hannan; Triantama, Febry (Journal of International Relations on Energy Affairs, 2024)
This research aimed to analyze the dynamics of United States arms sales to Taiwan. Taiwan as a country that is facing threats from China needs military technology weapons in maintaining its country's security. The conflict between China and Taiwan, namely territorial disputes, brought Taiwan to the United States as an ally and carried out defense cooperation by increasing arms sales to Taiwan. The United States has been carrying out arms sales since the era of President Jimmy Carter through the Regional Law, namely the Taiwan Relations Act (TRA) as the first step in cooperation in arms sales to Taiwan. The implementation was rejected by President Barack Obama over Taiwan's request for the sale of F-16C/D fighters. Using the Power and Influence theory The research focused on looking at how the United States sold the more advanced F-16 Viper fighter but previously rejected the sale of F-16C/Ds to Taiwan. The research methods used are descriptive qualitative methods and data collection through library research. The results of this study show a change in policy that there is a Security Dilemma in rejecting the F-16 C/D and selling an even more sophisticated F-16 Viper because there is Power and Influence through the actors involved and want to bring the United States to become an influential country in the world.